Comparative Analysis of Readability of Arabic Books Using Fry Ghraps and Fog Index (Taqdir, 2024)
Abstract This study aims to compare the readability of the textbook "Mari Belajar Bahasa Arab Madrasah Diniyah Takmiliyah Awaliyah untuk Kelas VI (Equivalent to Grade VI SD/MI)" using the Fry Graph and Fog Index. A descriptive method with a qualitative approach was used, involving content analysis based on data from the Fry Graph and Fog Index techniques. Data were collected through note-taking and literature studies, with purposive samples from three book segments (beginning, middle, and end). The Fry Graph results indicated that the book is more suitable for grades 2 to 4, not grades 6, due to its easy readability. Only the third passage matched the intended grade level, while the others could have been better. The Fog Index analysis yielded an average score of 1.9, placing it in the "Very Easy" category, failing to meet the ideal standard for grade 6. The low percentage of complex words (7%) shows that students have mastered most of the material, but the book needs to be more challenging.Keywords: Readability, Fry Graph, Fog Index